Highly thermally conductive self-repairing silicone thermal conductive gel and preparation method thereof
Patent Information
- Application Number
- CN202611363870.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]现有高导热凝胶技术存在明显缺陷,难以满足行业需求:
在本申请的实施例中,针对于现有技术中的硬度偏高、体系内部应力偏高、易产生微裂纹和气泡的技术问题,本申请提供了采用四峰级配填料与梯度核壳包覆技术构建低内应力导热骨架,配合增韧改性的解决方案,具体为:按质量份数计,包括:乙烯基聚二甲基硅氧烷100份;导热填料复合体系715~1220份;增韧剂1~5份;消泡剂0.2~0.3份;流平剂0.05~0.15份;铂催化剂0.2~0.5份;交联剂2~4份;阻聚剂0.03~0.08份;其中,所述导热填料复合体系包括四峰级配氮化铝、单峰氧化铝、四针状氧化锌晶须、纳米协同导热相和偶联剂。通过采用四峰级配氮化铝与单峰氧化铝、四针状氧化锌晶须及纳米协同导热相复配,构建了从纳米到微米级的多尺度、高效率导热网络,在导热系数≥14 W/m·K的条件下,彻底避免了金刚石高硬度对设备器件的损害;通过增韧剂与乙烯基聚二甲基硅氧烷基体的协同作用下,凝胶网络中的动态化学键或氢键作用得以增强,以愈合产品服役过程中产生的微裂纹;通过指定配比的导热填料复合体系及四峰级配比例,在保证高导热填料堆积密度最大化的同时,避免了填料过量导致的粘度急剧上升。
Smart Images

Figure CN122978725A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermally conductive gels, specifically to a highly thermally conductive and self-healing organosilicon thermally conductive gel and its preparation method. Background Technology
[0002] With the rapid development of high-power electronic devices such as 5G communication, new energy vehicles, AI servers, and 800V high-voltage electrical control, chip power consumption continues to increase, placing higher demands on the heat dissipation efficiency, mechanical properties, long-term reliability, and adaptability to automated construction of thermal interface materials. Thermal conductive gels, with their advantages of being soft and compressible and having good interface adhesion, have become a key heat dissipation material between chips and heat sinks, and are widely used in high-power devices and ultra-thin gap heat dissipation scenarios.
[0003] Existing high thermal conductivity gel technology has significant drawbacks and fails to meet industry demands: Thermal conductivity 14 W / m Products with a hardness of K or higher generally contain diamond, which has a high hardness and can easily damage chips, substrates, flexible devices, and dispensing equipment, posing a safety hazard in applications. In addition, the products also have limited packing density and high internal stress, which can easily lead to microcracks and bubbles during long-term service. Summary of the Invention
[0004] In view of the aforementioned problems, this application is made to provide a high thermal conductivity self-healing organosilicon thermally conductive gel and a method for preparing the same, which overcomes or at least partially solves the aforementioned problems, comprising: A highly thermally conductive and self-healing silicone thermally conductive gel, comprising, by weight parts: 100 parts of vinyl polydimethylsiloxane; 715–1220 parts of thermally conductive filler composite system; Toughening agent 1-5 parts; Defoamer 0.2-0.3 parts; Leveling agent 0.05–0.15 parts; Platinum catalyst 0.2–0.5 parts; 2-4 parts of crosslinking agent; Polymerization inhibitor 0.03–0.08 parts; The thermally conductive filler composite system includes a four-peak graded aluminum nitride, a single-peak alumina, four needle-like zinc oxide whiskers, a nano-synergistic thermally conductive phase, and a coupling agent.
[0005] Furthermore, by mass fraction, the thermally conductive filler composite system comprises 600-900 parts of the four-peak graded aluminum nitride, 80-200 parts of the single-peak alumina, 30-100 parts of the four-needle zinc oxide whiskers, 5-20 parts of the nano-synergistic thermally conductive phase, and 1-3 parts of the coupling agent.
[0006] Furthermore, the four-peak graded aluminum nitride has a D50 of 0.2–1 μm, 1–5 μm, 10–30 μm, and 70–120 μm, with a mass ratio of 5–10:10–20:30–50:40–60; the single-peak alumina has a D50 of 1 μm and a purity ≥99.9%; and the four needle-like zinc oxide whiskers have an aspect ratio of 5–20 and are oriented along the thickness direction.
[0007] Furthermore, the nano-synergistic thermally conductive phase is at least one of nano-h-BN and sheet-like alumina; the coupling agent is at least one of γ-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, and methyltrimethoxysilane.
[0008] Furthermore, the toughening agent is at least one of phenolic resin, nitrile rubber micro powder, acrylate rubber, polyvinyl butyral, and polyurethane; the defoamer is at least one of polyether defoamer, natural oil, higher alcohol, organosilicon defoamer, polyether-modified silicone, and polysiloxane defoamer; and the leveling agent is at least one of polymethylphenylsiloxane, polydimethylsiloxane, polyether polyester-modified organosilicon, alkyl-modified organosilicon, and acrylic leveling agent.
[0009] Furthermore, the concentration of the platinum catalyst is 2000-5000 ppm, and it is at least one of chloroplatinic acid and platinum-vinylsiloxane complex.
[0010] Furthermore, the crosslinking agent is a hydrogen-containing polysiloxane with a Si-H content of 0.6 to 1.0 wt%.
[0011] Furthermore, the polymerization inhibitor is at least one of long-chain silane-modified alkynol derivatives and long-chain maleic acid ester derivatives.
[0012] A method for preparing a highly thermally conductive and self-healing organosilicon thermally conductive gel includes the following steps: The vinyl polydimethylsiloxane, toughening agent, thermally conductive filler composite system, defoamer and leveling agent are mixed and stirred according to the specified ratio, while cooling water is circulated to maintain the temperature at 20-30℃ to obtain the mixture. The mixture is divided into two parts. One part is added with a platinum catalyst to obtain component A, and the other part is added with a crosslinking agent to obtain component B. The components A and B are mixed in a 1:1 ratio, pre-cured at a first specified temperature for a first specified time, and then cured at a second specified temperature for a second specified time to obtain the target silicone thermal conductive gel.
[0013] Furthermore, it also includes: Aluminum nitride was coated with a gradient core-shell structure using 1–3 nm SiO2-siloxane, and then the tetramodal aluminum nitride, aluminum oxide, zinc oxide whiskers, and nano-synergistic thermally conductive phase were modified with coupling agents, respectively. The four-peaked aluminum nitride, the alumina, the zinc oxide whiskers and the nano-synergistic thermally conductive phase are mixed and stirred according to the specified ratio, stirred at a first speed for a third specified time, and then stirred at a second speed for a fourth specified time to obtain the target thermally conductive filler composite system.
[0014] This application has the following advantages: In the embodiments of this application, addressing the technical problems of high hardness, high internal stress, and easy generation of microcracks and bubbles in the prior art, this application provides a solution that uses a four-peak graded filler and gradient core-shell coating technology to construct a low internal stress thermally conductive skeleton, combined with toughening modification. Specifically, by mass parts, it includes: 100 parts of vinyl polydimethylsiloxane; 715-1220 parts of thermally conductive filler composite system; 1-5 parts of toughening agent; 0.2-0.3 parts of defoamer; 0.05-0.15 parts of leveling agent; 0.2-0.5 parts of platinum catalyst; 2-4 parts of crosslinking agent; and 0.03-0.08 parts of polymerization inhibitor. The thermally conductive filler composite system includes four-peak graded aluminum nitride, unipeaked alumina, four-needle zinc oxide whiskers, a nano-synergistic thermally conductive phase, and a coupling agent. By employing a composite of four-peak graded aluminum nitride, single-peaked alumina, four-needle zinc oxide whiskers, and nano-synergistic thermally conductive phases, a multi-scale, high-efficiency thermally conductive network from the nanometer to the micrometer scale was constructed. Under the condition of thermal conductivity ≥14 W / m·K, the damage to equipment and devices caused by the high hardness of diamond was completely avoided. Through the synergistic effect of toughening agent and vinyl polydimethylsiloxane, the dynamic chemical bonds or hydrogen bonds in the gel network were enhanced to heal microcracks generated during product service. By using a specified ratio of thermally conductive filler composite system and four-peak graded ratio, the high thermal conductivity filler packing density was maximized while avoiding a sharp increase in viscosity caused by excessive filler. Attached Figure Description
[0015] To more clearly illustrate the technical solution of this application, the drawings used in the description of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0016] Figure 1 This is a flowchart illustrating the steps of a method for preparing a highly thermally conductive, self-healing organosilicon thermally conductive gel according to an embodiment of this application. Detailed Implementation
[0017] To make the objectives, features, and advantages of this application more apparent and understandable, the application will be further described in detail below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.
[0018] The inventors discovered through analysis of existing technologies that although diamond has an extremely high intrinsic thermal conductivity, its Mohs hardness is as high as 10. In practical applications, it can easily damage chip surfaces, ceramic substrates, flexible circuits, and precision dispensing equipment.
[0019] To achieve high thermal conductivity, filler mass fraction typically exceeds 85% of the total system, leading to a sharp increase in viscosity and decreased flowability. High-viscosity materials are not only difficult to precisely dispense on automated production lines, but they also easily trap air bubbles during preparation and curing, forming points of concentrated interfacial thermal resistance and reducing actual heat dissipation. Furthermore, excessively high viscosity also increases equipment wear and maintenance costs.
[0020] Silicone rubber networks with high crosslinking density have high rigidity. During thermal shock service, the internal stress caused by the mismatch in thermal expansion coefficients is difficult to release, which can easily lead to interface debonding or body cracking, ultimately resulting in thermal interface failure.
[0021] In addition, existing thermal conductive gel products have limited functionality, lack room temperature self-healing capabilities, and cannot automatically close microcracks generated during service.
[0022] Reference Figure 1 This application illustrates an embodiment of a high thermal conductivity self-healing organosilicon thermally conductive gel and its preparation method, comprising, by weight parts: 100 parts of vinyl polydimethylsiloxane; 715–1220 parts of thermally conductive filler composite system; Toughening agent 1-5 parts; Defoamer 0.2-0.3 parts; Leveling agent 0.05–0.15 parts; Platinum catalyst 0.2–0.5 parts; 2-4 parts of crosslinking agent; Polymerization inhibitor 0.03–0.08 parts; The thermally conductive filler composite system includes a four-peak graded aluminum nitride, a single-peak alumina, four needle-like zinc oxide whiskers, a nano-synergistic thermally conductive phase, and a coupling agent.
[0023] In the embodiments of this application, addressing the technical problems of high hardness, high internal stress, and easy generation of microcracks and bubbles in the prior art, this application provides a solution that uses a four-peak graded filler and gradient core-shell coating technology to construct a low internal stress thermally conductive skeleton, combined with toughening modification. Specifically, by mass parts, it includes: 100 parts of vinyl polydimethylsiloxane; 715-1220 parts of thermally conductive filler composite system; 1-5 parts of toughening agent; 0.2-0.3 parts of defoamer; 0.05-0.15 parts of leveling agent; 0.2-0.5 parts of platinum catalyst; 2-4 parts of crosslinking agent; and 0.03-0.08 parts of polymerization inhibitor. The thermally conductive filler composite system includes four-peak graded aluminum nitride, unipeaked alumina, four-needle zinc oxide whiskers, a nano-synergistic thermally conductive phase, and a coupling agent. By employing a composite of four-peak graded aluminum nitride, single-peaked alumina, four-needle zinc oxide whiskers, and nano-synergistic thermally conductive phases, a multi-scale, high-efficiency thermally conductive network from the nanometer to the micrometer scale was constructed. Under the condition of thermal conductivity ≥14 W / m·K, the damage to equipment and devices caused by the high hardness of diamond was completely avoided. Through the synergistic effect of toughening agent and vinyl polydimethylsiloxane, the dynamic chemical bonds or hydrogen bonds in the gel network were enhanced to heal microcracks generated during product service. By using a specified ratio of thermally conductive filler composite system and four-peak graded ratio, the high thermal conductivity filler packing density was maximized while avoiding a sharp increase in viscosity caused by excessive filler.
[0024] The following will further describe a highly thermally conductive, self-healing silicone thermally conductive gel in this exemplary embodiment.
[0025] Specifically, vinyl polydimethylsiloxane serves as the base compound, providing the main chain backbone of silicone rubber. For example, vinyl polydimethylsiloxane can be end vinyl polydimethylsiloxane or polydimethylsiloxane with vinyl side chains.
[0026] In one embodiment of the present invention, the thermally conductive filler composite system comprises, by mass parts, 600-900 parts of the four-peak graded aluminum nitride, 80-200 parts of the single-peak alumina, 30-100 parts of the four-needle zinc oxide whiskers, 5-20 parts of the nano-synergistic thermally conductive phase, and 1-3 parts of the coupling agent.
[0027] Specifically, four-peak graded aluminum nitride is the main thermally conductive filler, forming the core component of the thermally conductive filler composite system and providing the main thermal conduction channels. Single-peaked alumina is used to fill the microscopic voids left after the four-peaked aluminum nitride gradation, increasing the packing density. Four-needle zinc oxide whiskers utilize their three-dimensional four-needle structure to form directional thermal conduction pathways in the thickness direction. A nano-synergistic thermally conductive phase acts as a nanoscale thermal bridge, connecting the interfacial gaps between micron-sized fillers. A coupling agent is used to organically modify the surface of all fillers, improving the interfacial compatibility between the fillers and the silicon matrix. By combining four-peaked graded aluminum nitride, single-peaked alumina, and directionally arranged four-needle zinc oxide whiskers, and adding trace amounts of synergistic thermally conductive phase, and performing SiO2-siloxane gradient core-shell coating treatment on aluminum nitride, the compatibility and hydrolysis resistance of the fillers are improved, constructing efficient vertical thermal conduction pathways and achieving high thermal conductivity without diamond.
[0028] As an example, the amount of tetra-peaked graded aluminum nitride can be 600 kg, 750 kg, 800 kg, 850 kg or 900 kg; the amount of uni-peaked alumina can be 80 kg, 100 kg, 120 kg, 150 kg, 180 kg or 200 kg; the amount of tetra-needle-shaped zinc oxide whiskers can be 30 kg, 60 kg, 90 kg or 100 kg; the amount of nano-synergistic thermally conductive phase can be 5 kg, 10 kg, 15 kg or 20 kg; and the amount of coupling agent can be 1 kg, 2 kg or 3 kg.
[0029] In one embodiment of the present invention, the four-peak graded aluminum nitride has a D50 of 0.2–1 μm, 1–5 μm, 10–30 μm, and 70–120 μm, with a mass ratio of 5–10:10–20:30–50:40–60; the single-peak alumina has a D50 of 1 μm and a purity of ≥99.9%; and the four needle-like zinc oxide whiskers have an aspect ratio of 5–20 and are oriented along the thickness direction.
[0030] Specifically, the four-peak graded aluminum nitride uses four powders with different median particle sizes (D50). Through the stepwise filling of particles of different sizes, the packing density is maximized, forming a continuous and dense thermal conductivity pathway. The unimodal alumina has a D50 of 1 μm and a purity of ≥99.9%, serving as a secondary filler phase to fill the microscopic gaps after the four-peak aluminum nitride is graded. The tetraneedle-shaped zinc oxide whiskers have a three-dimensional tetraneedle structure with an aspect ratio of 5–20, and are oriented along the thickness direction, enabling the construction of efficient longitudinal thermal conductivity bridges in the direction perpendicular to the substrate. As examples, 0.2–1 μm can be 0.2 μm, 0.5 μm, 0.8 μm, or 1 μm; 1–5 μm can be 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm; 10–30 μm can be 10 μm, 20 μm, or 30 μm; and 70–120 μm can be 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, or 120 μm. The aspect ratio of the tetraneedle-shaped zinc oxide whiskers can be 5, 10, 15, or 20.
[0031] In one embodiment of the present invention, the nano-synergistic thermally conductive phase is at least one of nano-h-BN and lamellar alumina; the coupling agent is at least one of γ-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, and methyltrimethoxysilane. Nano-h-BN (hexagonal boron nitride) has a two-dimensional lamellar structure and high intrinsic thermal conductivity, and can act as a thermally conductive bridge connecting adjacent micron-sized filler particles at the nanoscale; lamellar alumina also has two-dimensional geometric features, which can complement the three-dimensional structure of tetrapter-shaped zinc oxide whiskers, synergistically constructing a thermally conductive network. The coupling agent preferred in this application is γ-glycidoxypropyltrimethoxysilane.
[0032] In one embodiment of the present invention, the toughening agent is at least one of phenolic resin, nitrile rubber micro powder, acrylate rubber, polyvinyl butyral, and polyurethane; the defoamer is at least one of polyether defoamer, natural oil, higher alcohol, organosilicon defoamer, polyether-modified silicone, and polysiloxane defoamer; and the leveling agent is at least one of polymethylphenylsiloxane, polydimethylsiloxane, polyether polyester-modified organosilicon, alkyl-modified organosilicon, and acrylic leveling agent.
[0033] Specifically, the toughening agent is used to absorb and disperse internal stress in the system and improve crack resistance, and is preferably a phenolic resin; the defoamer is used to remove air bubbles trapped during mixing and curing, and is preferably a polyether-modified silicone defoamer; the leveling agent is used to improve the spreadability and wettability of the system on the substrate surface, and is preferably an alkyl-modified silicone.
[0034] In one embodiment of the present invention, the concentration of the platinum catalyst is 2000–5000 ppm, and it is at least one of chloroplatinic acid and platinum-vinylsiloxane complex. 2000–5000 ppm refers to the mass concentration of platinum in the catalyst solution. As a catalyst for addition reactions, the concentration of the platinum catalyst directly affects the reaction rate and curing efficiency.
[0035] In one embodiment of the present invention, the crosslinking agent is a hydrogen-containing polysiloxane with a Si-H content of 0.6–1.0 wt%. The crosslinking agent undergoes a hydrosilylation reaction with vinyl groups to form a crosslinking network. The Si-H bonds on the hydrogen-containing polysiloxane molecular chain and the vinyl groups (CH=CH2) on the vinyl polydimethylsiloxane molecular chain undergo an addition reaction under platinum catalysis to form a Si-CH2-CH2-siloxane crosslinking network. As an example, the hydrogen-containing polysiloxane can be any one or a combination of terminal hydrogen-containing polysiloxanes, side-chain hydrogen-containing polysiloxanes, or polysiloxanes containing hydrogen at both ends and sides.
[0036] In one embodiment of the present invention, the polymerization inhibitor is at least one of an alkynyl alcohol derivative and a maleic ester derivative.
[0037] Specifically, polymerization inhibitors are used to regulate the reaction rate and extend the workability of the system. By forming a coordination complex with the platinum catalyst, the inhibitor temporarily "poisons" the catalytic active center at room temperature, reducing the reaction rate and extending the workability of the system. When the temperature rises to the curing temperature, the complex dissociates, releasing the catalytic activity and achieving high-temperature rapid curing. Conventional small-molecule single alkynols are merely ordinary polymerization inhibitors and cannot achieve the high-efficiency standard. High-efficiency polymerization inhibitors can form stable coordination complexes with the platinum catalyst at room temperature; the workability of the mixed adhesive at 25°C is ≥5 hours; the viscosity increase after 3 months of refrigeration at 0–8°C is ≤30%; the thermal desealing range is 100–140°C; the gradient preheating stage does not result in premature local curing; and there are no volatile bubbles throughout the curing process. As an example, the polymerization inhibitor can be a long-chain silane-modified alkynyl alcohol derivative such as ethynylcyclohexanol (ECH) or methylbutynyl alcohol (MBY), or a long-chain maleic ester derivative such as diethyl maleate or dibutyl maleate, or a combination of both. The high-efficiency polymerization inhibitor of this invention requires only 0.03–0.08 parts, has good compatibility with highly filled aluminum nitride fillers, will not be adsorbed and deactivated by powder, and exhibits no significant attenuation in the finished product's thermal conductivity, breakdown voltage, and damp heat stability, making it fully compatible with automated coating and gradient curing processes.
[0038] Reference Figure 1 This paper demonstrates a method for preparing a highly thermally conductive, self-healing silicone thermally conductive gel, comprising the following steps: S110. Mix and stir vinyl polydimethylsiloxane, toughening agent, thermally conductive filler composite system, defoamer and leveling agent according to the specified ratio, while cooling water is circulated to maintain the temperature at 20-30℃ to obtain the mixture. S120. Divide the mixture into two parts, add a platinum catalyst to one part to obtain component A, and add a crosslinking agent to the other part to obtain component B; S130. Mix component A and component B in a 1:1 ratio, pre-cur at a first specified temperature for a first specified time, and then cure at a second specified temperature for a second specified time to obtain the target silicone thermal conductive gel.
[0039] In an embodiment of the present invention, vinyl polydimethylsiloxane is used as the base adhesive, combined with a platinum catalyst, hydrogen-containing polysiloxane, and a high-efficiency polymerization inhibitor. A thermally conductive filler composite system, toughening agent, defoamer, and leveling agent are added. The mixture is prepared in groups and components, and a four-stage vacuum mixing + ultrasonic-assisted dispersion + three-roll milling + gradient curing process is used to obtain a diamond-free, high thermal conductivity, self-healing organosilicon thermally conductive gel.
[0040] The preparation method of a high thermal conductivity self-healing organosilicon thermally conductive gel in this exemplary embodiment will be further described below.
[0041] In one embodiment of the present invention, the specific process of step S110, which involves "mixing and stirring vinyl polydimethylsiloxane, toughening agent, thermally conductive filler composite system, defoamer and leveling agent according to a specified ratio, while maintaining the temperature at 20-30°C by purging with cooling water, to obtain a mixture", can be further described in conjunction with the following description.
[0042] As an example, the mixing equipment can be any of a planetary mixer, a double planetary disperser, a vacuum kneader, or a high-speed disperser. Temperature control methods, besides cooling water in the jacket, can also be achieved by controlling the mixing speed, intermittent mixing, or using a dispersing disc with cooling capabilities.
[0043] In one specific implementation, 100 kg of vinyl polydimethylsiloxane and 2 kg of toughening agent are first added to a planetary mixer at a speed of 30 r / min for 20–30 min, then the speed is adjusted to 50 r / min and stirred for 120–150 min until completely dissolved; the thermally conductive filler composite system is added at a speed of 30 r / min for 10–20 min, then the speed is adjusted to 50 r / min and stirred for 20–30 min, coupled with 20–40 kHz ultrasonic-assisted dispersion; the defoamer and leveling agent are added at a speed of 30 r / min and stirred for 30–40 min, while cooling water is circulated to maintain the temperature at 20–30 °C to prevent premature reaction.
[0044] In one embodiment of the present invention, the specific process of step S120, "dividing the mixture into two parts, adding a platinum catalyst to one part to obtain component A, and adding a crosslinking agent to the other part to obtain component B", can be further described in conjunction with the following description.
[0045] Divide the mixture into two parts according to a specified ratio. The specified ratio can be equal parts by mass or non-mass parts. Divide the material into two parts. Add a platinum catalyst to one part to obtain component A, and add a hydrogen-containing polysiloxane and a high-efficiency polymerization inhibitor to the other part to obtain component B. Stir each part at 30 r / min for 10-20 min, and control the temperature at 20-30℃. Components A and B are respectively ground three times with a three-roll mill, filtered through a 100-500 mesh filter (preferably a 200 mesh filter), and vacuum degassed for 20 min, with a vacuum degree ≤-0.098MPa.
[0046] In one embodiment of the present invention, the specific process of step S130, "dividing the mixture into two parts, adding a platinum catalyst to one part to obtain component A, and adding a crosslinking agent to the other part to obtain component B", can be further described in conjunction with the following description.
[0047] As an example, the first specified temperature can be 70–90°C, and the first specified time can be 5–20 minutes; the second specified temperature can be 90–110°C, and the second specified time can be 15–30 minutes. The curing equipment can be any one of a constant temperature oven, a tunnel curing oven, or a hot press. The mixing method can be static mixing tube online mixing, manual stirring mixing, or low-speed mechanical stirring mixing.
[0048] In one specific implementation, components A and B are mixed in a 1:1 ratio and gradient curing is adopted: pre-curing at 80℃ for 10 min, deep curing at 100℃ for ≤25 min, and post-curing at room temperature for 2 h to obtain the finished product.
[0049] In one embodiment of the present invention, it further includes: Aluminum nitride was coated with a gradient core-shell structure using 1–3 nm SiO2-siloxane, and then the tetramodal aluminum nitride, aluminum oxide, zinc oxide whiskers, and nano-synergistic thermally conductive phase were modified with coupling agents, respectively. The four-peaked aluminum nitride, the alumina, the zinc oxide whiskers and the nano-synergistic thermally conductive phase are mixed and stirred according to the specified ratio, stirred at a first speed for a third specified time, and then stirred at a second speed for a fourth specified time to obtain the target thermally conductive filler composite system.
[0050] Specifically, aluminum nitride is first coated with a 1-3 nm SiO2-siloxane gradient core-shell structure, then all fillers are modified with a coupling agent and vacuum dried at 120°C for 2 hours. The four-peak aluminum nitride, alumina, zinc oxide whiskers, and nano-synergistic thermally conductive phase are added to a planetary mixer according to the formula, stirred at 30 r / min for 20-30 min, then the speed is adjusted to 50 r / min and stirred for 120-150 min to obtain a thermally conductive filler composite system for later use.
[0051] The following are specific embodiments. Example 1 Thermally conductive filler composite system: 750 kg of tetra-peaked aluminum nitride, 150 kg of alumina, 60 kg of zinc oxide whiskers, 10 kg of nano-h-BN, and 2 kg of γ-glycidyl etheroxypropyltrimethoxysilane, modified and premixed according to the aforementioned method; Base adhesive mixing: 100 kg of vinyl polydimethylsiloxane and 2 kg of phenolic resin, stirred and dissolved; Filler addition: Add the above thermally conductive filler composite system and disperse evenly with ultrasonic assistance; Additives: Add 0.25 kg of polyether-modified organosilicon defoamer and 0.1 kg of alkyl-modified organosilicon, stir evenly, and control the temperature at 20-30℃; Group preparation: Divide the materials evenly, add 0.3 kg of chloroplatinic acid to component A, and add 2.5 kg of hydrogen-containing polysiloxane and 0.05 kg of acetylenecyclohexanol to component B; Post-processing: Three-roll milling three times, 200-mesh filtration, vacuum degassing; Curing: Mix components A and B in a 1:1 ratio, cure at 80℃ for 10 min + 100℃ for 25 min + room temperature for 2 h to obtain a thermally conductive gel, and store at 0~8℃.
[0052] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0053] Example 2 600 kg of tetra-peaked aluminum nitride, the rest is the same as in Example 1.
[0054] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0055] Example 3 900 kg of tetra-peaked aluminum nitride, the rest is the same as in Example 1.
[0056] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0057] Example 4 The phenol-oxygen resin content was 1.5 kJ, and the rest was the same as in Example 1.
[0058] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0059] Example 5 2.5 kg of phenolic resin, the rest is the same as in Example 1.
[0060] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0061] Example 6 Component B is supplemented with 2 kg of hydrogen-containing polysiloxane, and the rest is the same as in Example 1.
[0062] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0063] Example 7 Component B is supplemented with 4 kg of hydrogen-containing polysiloxane, and the rest is the same as in Example 1.
[0064] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0065] Example 8 Component A is supplemented with 0.2 kg of chloroplatinic acid, and the rest is the same as in Example 1.
[0066] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0067] Example 9 Component A is supplemented with 0.5 kg of chloroplatinic acid, and the rest is the same as in Example 1.
[0068] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0069] Example 10 The ingredients are: 850 kg of tetra-peaked aluminum nitride, 120 kg of aluminum oxide, 50 kg of zinc oxide whiskers, 8 kg of nano-h-BN, and 3 kg of γ-glycidyl etheroxypropyltrimethoxysilane. The rest are the same as in Example 1.
[0070] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0071] Example 11 900 kg of tetra-peaked aluminum nitride, 180 kg of aluminum oxide, 70 kg of zinc oxide whiskers, 15 kg of nano-h-BN, and 3 kg of γ-glycidyl etheroxypropyltrimethoxysilane, with the remainder being the same as in Example 1.
[0072] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0073] Comparative Example 1 750 kg of tri-peaked aluminum nitride, the rest is the same as in Example 1.
[0074] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0075] Comparative Example 2 Aluminum nitride is not subjected to core-shell coating treatment; otherwise, it is the same as in Example 1.
[0076] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0077] Comparative Example 3 The zinc oxide whiskers are arranged in an irregular pattern, and the rest is the same as in Example 1.
[0078] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0079] Comparative Example 4 The conventional alkynol inhibitor 1-ethynylcyclohexanol 0.05 kg was used, and the rest was the same as in Example 1.
[0080] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0081] Comparative Example 5 No defoamer was added. A non-vacuum mixing process was used to stir the mixture evenly and control the temperature at 20-30°C. The rest of the process was the same as in Example 1.
[0082] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0083] Comparative Example 6 Nano-h-BN was replaced with diamond filler, and the rest was the same as in Example 1.
[0084] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0085] Comparative Example 7 The thermally conductive filler uses only alumina, and the rest is the same as in Example 1.
[0086] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0087] Comparative Example 8 The vinyl polydimethylsiloxane was replaced with methylphenyl silicone rubber, and the rest was the same as in Example 1.
[0088] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0089] Comparative Example 9 Phenoxy resin was not added; otherwise, it was the same as in Example 1.
[0090] The prepared thermally conductive gels were characterized by their thermal conductivity, thermal resistance, viscosity, shear strength, breakdown voltage, self-healing properties, and curing bubbles. The results are shown in Table 1.
[0091] Performance testing: Thermal conductivity was tested according to ASTM D5470; Thermal resistance was tested according to ASTM D5470; The breakdown voltage was tested according to ASTM D149; Shear strength was tested according to ASTM D1002; Viscosity was measured using a rotational viscometer; Self-healing performance: Microcrack healing was observed at room temperature for 24 hours; Curing bubbles: Visual inspection and microscopic observation of the state after high-temperature curing; Damp heat aging: Performance retention rate was tested after aging at 85℃ / 85% RH for 1000 hours.
[0092] Table 1
[0093] The statistical data in Table 1 above shows that the diamond-free, high thermal conductivity, self-healing silicone thermal gel of the present invention not only achieves a thermal conductivity of ≥14.0 W / m without diamonds. K also possesses excellent shear strength, insulation properties, room temperature self-healing ability, high-temperature curing without bubbles, strong stability during humid heat aging, and long working time, fully meeting the requirements of automated production and automotive-grade high-reliability use.
[0094] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.
[0095] Finally, it should be noted that in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or terminal device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or terminal device. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or terminal device that includes said element.
[0096] The above provides a detailed description of a high thermal conductivity self-healing organosilicon thermally conductive gel and its preparation method. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A highly thermally conductive, self-healing organosilicon thermally conductive gel, characterized in that, By weight, including: 100 parts of vinyl polydimethylsiloxane; 715–1220 parts of thermally conductive filler composite system; Toughening agent 1-5 parts; Defoamer 0.2-0.3 parts; Leveling agent 0.05–0.15 parts; Platinum catalyst 0.2–0.5 parts; 2-4 parts of crosslinking agent; Polymerization inhibitor 0.03–0.08 parts; The thermally conductive filler composite system includes a four-peak graded aluminum nitride, a single-peak alumina, four needle-like zinc oxide whiskers, a nano-synergistic thermally conductive phase, and a coupling agent.
2. The high thermal conductivity self-healing organosilicon thermally conductive gel according to claim 1, characterized in that, By mass fraction, the thermally conductive filler composite system comprises 600-900 parts of the four-peak graded aluminum nitride, 80-200 parts of the single-peak alumina, 30-100 parts of the four-needle zinc oxide whiskers, 5-20 parts of the nano-synergistic thermally conductive phase, and 1-3 parts of the coupling agent.
3. The high thermal conductivity self-healing organosilicon thermally conductive gel according to claim 1, characterized in that, The four-peak graded aluminum nitride has a D50 of 0.2–1 μm, 1–5 μm, 10–30 μm, and 70–120 μm, with a mass ratio of 5–10:10–20:30–50:40–60; the single-peak alumina has a D50 of 1 μm and a purity of ≥99.9%; the four needle-like zinc oxide whiskers have an aspect ratio of 5–20 and are oriented along the thickness direction.
4. The high thermal conductivity self-healing organosilicon thermally conductive gel according to claim 1, characterized in that, The nano-synergistic thermally conductive phase is at least one of nano-h-BN and sheet-like alumina; the coupling agent is at least one of γ-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, and methyltrimethoxysilane.
5. The high thermal conductivity self-healing organosilicon thermally conductive gel according to claim 1, characterized in that, The toughening agent is at least one of phenolic resin, nitrile rubber powder, acrylate rubber, polyvinyl butyral, and polyurethane; the defoamer is at least one of polyether defoamer, natural oil, higher alcohol, organosilicon defoamer, polyether-modified silicone, and polysiloxane defoamer; the leveling agent is at least one of polymethylphenylsiloxane, polydimethylsiloxane, polyether polyester-modified organosilicon, alkyl-modified organosilicon, and acrylic leveling agent.
6. The high thermal conductivity self-healing organosilicon thermally conductive gel according to claim 1, characterized in that, The platinum catalyst has a concentration of 2000–5000 ppm and is at least one of chloroplatinic acid and platinum-vinylsiloxane complex.
7. The high thermal conductivity self-healing organosilicon thermally conductive gel according to claim 1, characterized in that, The crosslinking agent is a hydrogen-containing polysiloxane with a Si-H content of 0.6 to 1.0 wt%.
8. The high thermal conductivity self-healing organosilicon thermally conductive gel according to claim 1, characterized in that, The polymerization inhibitor is at least one of long-chain silane-modified alkynol derivatives and long-chain maleic acid ester derivatives.
9. A method for preparing a highly thermally conductive, self-healing organosilicon thermally conductive gel, characterized in that, Including the following steps: The vinyl polydimethylsiloxane, toughening agent, thermally conductive filler composite system, defoamer and leveling agent are mixed and stirred according to the specified ratio, while cooling water is circulated to maintain the temperature at 20-30℃ to obtain the mixture. The mixture is divided into two parts. One part is added with a platinum catalyst to obtain component A, and the other part is added with a crosslinking agent to obtain component B. The components A and B are mixed in a 1:1 ratio, pre-cured at a first specified temperature for a first specified time, and then cured at a second specified temperature for a second specified time to obtain the target silicone thermal conductive gel.
10. The method for preparing the high thermal conductivity self-healing organosilicon thermally conductive gel according to claim 9, characterized in that, Also includes: Aluminum nitride was coated with a gradient core-shell structure using 1–3 nm SiO2-siloxane, and then the tetramodal aluminum nitride, aluminum oxide, zinc oxide whiskers, and nano-synergistic thermally conductive phase were modified with coupling agents, respectively. The four-peaked aluminum nitride, the alumina, the zinc oxide whiskers and the nano-synergistic thermally conductive phase are mixed and stirred according to the specified ratio, stirred at a first speed for a third specified time, and then stirred at a second speed for a fourth specified time to obtain the target thermally conductive filler composite system.